Advancing Research Alongside Patient Partners: Next-Generation Best Practices for Effective Collaboration in Health Research - Ally C. Farrell; Jessica A. Lawson; Ovarian Cancer Canada’s Patient Partners in Research Team; Alison Ross; Alicia A. Tone (Current Oncology, 2024)
Ovarian Cancer Canada’s Patient Partners in Research (PPiR) is a national volunteer-based program that trains and connects individuals with lived ovarian cancer (OC) experience to diverse research opportunities, to maximize the clinical relevance and real-life impact of OC research in Canada. A steadily increasing demand for patient partners to be involved as research team members and decision-makers led us to co-develop with the PPiR team a series of “best practices” for researcher–patient partnerships. This framework formalizes our evolving approach to patient engagement and begins to address challenges that can arise in research settings focused on less commonly diagnosed yet significant and fatal diseases such as OC: (1) Start early. (2) Foster collaboration among the entire research team. (3) Establish expectations and communicate regularly. (4) Report impact of patient partner contributions. (5) Ensure adequate resources. While there are ongoing challenges associated with patient engagement that need to be addressed, data collected from an anonymous survey of Canadian OC researchers show a marked improvement in perceived benefits of patient engagement over time and validate the best practices presented herein. Developed in the context of OC research, these best practices can be adapted to a variety of health research settings with similar challenges.